The impact of family visitor restrictions on healthcare workers in the ICU during the COVID-19 pandemic. (February 2022) - Wendlandt, Blair; Kime, Mary; Carson, Shannon
Abstract: Purpose: To obtain information on how family visitor restriction during the COVID-19 pandemic has impacted the workplace experience of physicians and nurses in the medical intensive care unit, and to assess differences by profession. Materials and methods: We developed a survey containing closed- and open-ended questions, applying both quantitative and qualitative analyses to our results. Results: Of the 74 respondents, 29 (38%) were nurses and 45 (62%) were physicians. Nurses reported positive changes to daily workflow and the ability to provide medical care, while physicians reported negative changes in these areas. Both groups reported decreased comprehension and increased distress among families, and decreased ability to provide end-of-life care. For the qualitative analysis, eight themes were identified: the patient's room as space, creation of a new space through virtual communication, time, increased complexity of care, challenges around the use of technology, adjustments to team roles and responsibilities, desire for families to return, and internal tension. Conclusion: Intensive care physicians and nurses reported both positive and negative effects of family visitor restriction during the COVID-19 pandemic, with significant differences based on profession. Both groups expressed concern for an overall negative impact of visitor restriction on healthcare workers, patients, and their families.